Analisis Pemberian Reward Dan Punishment Untuk Memotivasi Belajar Pada Pembelajaran Geografi Kelas X Di SMA Taman MuliaTex - Rumanti, Rumanti; Asriati, Nuraini; Adlika, Nur Meily (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study was to find out about the Analysis of Giving Rewards and Punishments to Motivate Learning in Class X Geography at Taman Mulia High School. The type of research used is descriptive research with qualitative methods. Data collection techniques used are direct observation techniques, interviews and documentation. The instruments used are observation guidelines, interview guidelines and documentation guidelines. The results of this study are 1) Giving rewards can motivate learning in class X geography learning at Taman Mulia High School, 2) Giving punishment can motivate learning in class X learning geography at Taman Mulia High School, 3) Giving reward and punishment together can motivating learning in geography class X at Taman Mulia High School